Associations between empathizing-systemizing cognitive style and mental rotation task performance among homosexual men and women in China. (1st February 2017) - Zheng, Lijun; Zheng, Yong
Abstract: Empathizing-systemizing cognitive style is related to mental rotation ability among heterosexuals. We sought to determine whether there is also an association between a measure of empathizing-systemizing and mental rotation task performance via the Internet among homosexual men and women (372 men and 469 women) in China. We found that systemizing, but not empathizing, scores were positively correlated with mental rotation task performance in both homosexual men and women. When comparing by cognitive style, we found that homosexual individuals with a systemizing cognitive style performed significantly better on the mental rotation task than did those with an empathizing style. Our results indicate a consistency across cultures and sexual orientations in the association between systemizing and mental rotation task performance. Highlights: We examined the relationships between empathizing-systemizing and mental rotation. Systemizing was positively correlated with mental rotation in gay and lesbians. There was no significant association between empathizing and mental rotation. People with S cognitive style performed better on mental rotation than those with E.